Citation Analysis of Turkish Librarianship Journals - Doğan Atılgan; Cemal Atakan; Burcu Bulut (Türk Kütüphaneciliği)
A citation is one of the major measures that evaluates the scientific journals re- putability, reliability and usability in the international arena. The rate of the citation of a journal is a significant criterion for that particular journals scientific evaluation. Together with the scientific value of the journal, the citations used in an article are important benchmarks for the assessment of that article. In this paper, citations of peer reviewed articles from two library and information scien- ce journals which are published by Turkish professional associations and inde- xed in the international databases are going to be analyzed.